Review: Kletus Likuwa, Voices from the Kavango. A Study of the Contract Labour System in Namibia, 1925–1972, Basel, Basler Afrika Bibliographien, 2020 (Journal of Namibian Studies : History Politics Culture, 2021)
Review of: Kletus Likuwa, Voices from the Kavango. A Study of the Contract Labour System in Namibia, 1925–1972, Basel, Basler Afrika Bibliographien, 2020.